C/SiO2 meta-composite: Overcoming the λ/a relationship limitation in metamaterials. (December 2017) - Xie, Peitao; Zhang, Zidong; Liu, Kunpeng; Qian, Lei; Dang, Feng; Liu, Yao; Fan, Runhua; Wang, Xiaolin; Dou, Shixue
Abstract: Metamaterials usually require that the unit size a should be comparable to the wavelength λ . Although the λ / a relationship could tell us what size of unit we need and which method we should choose for the fabrication, it limits the application of metamaterials in the kHz and MHz frequency range, as the unit size would be on the order of 10 2  m, making the overall size of the metamaterial too large for practical application. In this paper, we firstly demonstrate that the λ / a relationship limitation could be overcome by a new kind of composite, which we have called carbon-based 'meta-composite'. A SiO2 matrix with periodic microstructure is fabricated by using self-assembly of SiO2 microspheres, and amorphous carbon fills in the gaps to form a three-dimensional periodic carbon network. The experimental results indicate that the carbon network will introduce tunable electromagnetic properties, which could be precisely tailored by controlling the geometric size of the carbon network. It is worth pointing out that the unit size of the periodic carbon network is on the sub-micrometre level, but the wavelength is on the order of 10 2  m. This means that the meta-composite overcomes the λ / a relationship limitation in the kHz and MHz frequency range, which shows great potential for the miniaturization of electronic devices. Graphical abstract: